2018
DOI: 10.19080/adoh.2018.09.555763
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Level of TNF- α In Chronic Periodontitis Patients with Gestational Diabetes Mellitus after Phase I Periodontal Therapy

Abstract: When adipose tissue inflammation and dysfunction are established, adipokine secretion is significantly changed toward a diabetogenic, proinflammatory and atherogenic pattern. TNF-α is a pro-inflammatory cytokine that plays a central role in inflammatory reaction, alveolar bone resorption, and the loss of connective tissue attachment. It is positively correlated with Matrix metalloproteinases (MMPs), Prostaglandin E2 (PGE2) and nuclear factor kappa [8-10] ligand (RANKL) expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…25 The results of research performed on rats showed that TNF-α levels decreased in periodontic experimental animals that received DM and dietary treatment. 26 In addition, based on the results of a study, 27 it was found that TNF-α had a significant relationship with periodontitis and type 2 DM in patients who received treatment. There was a decrease in TNF-α levels after drug consumption.…”
Section: Discussionmentioning
confidence: 99%
“…25 The results of research performed on rats showed that TNF-α levels decreased in periodontic experimental animals that received DM and dietary treatment. 26 In addition, based on the results of a study, 27 it was found that TNF-α had a significant relationship with periodontitis and type 2 DM in patients who received treatment. There was a decrease in TNF-α levels after drug consumption.…”
Section: Discussionmentioning
confidence: 99%